2007
DOI: 10.1001/archpsyc.64.5.543
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime and 12-Month Prevalence of Bipolar Spectrum Disorder in the National Comorbidity Survey Replication

Abstract: Context: There is growing recognition that bipolar disorder (BPD) has a spectrum of expression that is substantially more common than the 1% BP-I prevalence traditionally found in population surveys.Objective: To estimate the prevalence, correlates, and treatment patterns of bipolar spectrum disorder in the US population.Design: Direct interviews.Setting: Households in the continental United States.Participants: A nationally representative sample of 9282 English-speaking adults (aged Ն18 years).Main Outcome Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

68
1,361
14
53

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 2,115 publications
(1,496 citation statements)
references
References 52 publications
68
1,361
14
53
Order By: Relevance
“…In our study, 61% of the participants were female, similar to several other recently published large studies, which found rates from 55% to 70% (19,22–26). The BDCP participants’ mean age at onset of bipolar disorder was 20.8 years, which matches nationwide epidemiologic studies, such as the Epidemiologic Catchment Area study, the National Comorbidity Survey replication, and other studies, all of which found a mean age at onset between 19.8 and 22.9 years (22,24,25,2729). …”
Section: Discussionsupporting
confidence: 79%
“…In our study, 61% of the participants were female, similar to several other recently published large studies, which found rates from 55% to 70% (19,22–26). The BDCP participants’ mean age at onset of bipolar disorder was 20.8 years, which matches nationwide epidemiologic studies, such as the Epidemiologic Catchment Area study, the National Comorbidity Survey replication, and other studies, all of which found a mean age at onset between 19.8 and 22.9 years (22,24,25,2729). …”
Section: Discussionsupporting
confidence: 79%
“…As described in Section 6, patients diagnosed with BD very commonly have one or more comorbid psychiatric diagnoses, with SUDs, impulse control disorders, anxiety disorders, and personality disorders (especially cluster B disorders) particularly common 45. The presence of comorbidity increases the complexity of the illness and can make an accurate diagnosis even more difficult.…”
Section: Foundations Of Managementmentioning
confidence: 99%
“…The most common comorbid conditions are substance use disorder, anxiety disorder, personality disorder, and impulse control disorder (such as ADHD, ODD, and CD) 45. Comorbidity impacts the course of BDs by increasing the likelihood of treatment resistance and suicide risk, and also by increasing the time spent with impairing symptoms 34, 50, 669, 670…”
Section: Specific Populationsmentioning
confidence: 99%
“…BD typically begins in adolescence or early adulthood and can have life‐long adverse effects on the patient's mental and physical health, educational and occupational functioning, and interpersonal relationships (Valente & Kennedy, 2010). Although not as common as major depressive disorder (MDD), the lifetime prevalence of BD in the United States is substantial (estimated at approximately 4%), with similar rates regardless of race, ethnicity, and gender (Ketter, 2010; Merikangas et al., 2007). Long‐term outcomes are persistently suboptimal (Geddes & Miklowitz, 2013).…”
Section: Introductionmentioning
confidence: 99%